2008
DOI: 10.1093/hmg/ddn121
|View full text |Cite
|
Sign up to set email alerts
|

Variation in WNT genes is associated with non-syndromic cleft lip with or without cleft palate

Abstract: Non-syndromic cleft lip with or without cleft palate (NSCLP) is a common birth defect. Genetic and environmental factors have been causally implicated and studies have begun to delineate genetic contributions. The Wnt genes are involved in regulating mid-face development and upper lip fusion and are therefore strong candidates for an etiological role in NSCLP. Furthermore, the clf1 region in A/WyN clefting susceptible mice contains the Wnt3 and Wnt9B genes. To assess the role of the Wnt family of genes in NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
161
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(178 citation statements)
references
References 47 publications
5
161
2
10
Order By: Relevance
“…Our results continued to support the theory that the WNT3 genes may be associated with the occurrence of NSCL/P. This report details supplemental research of a previous study (Chiquet et al, 2008), and may be helpful in extending our understanding of the etiology of NSCL/P.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results continued to support the theory that the WNT3 genes may be associated with the occurrence of NSCL/P. This report details supplemental research of a previous study (Chiquet et al, 2008), and may be helpful in extending our understanding of the etiology of NSCL/P.…”
Section: Discussionsupporting
confidence: 83%
“…A previous study reported that among the 13 SNPs investigated in the WNT3A, WNT5A, WNT8A, WNT11, WNT3, and WNT9B genes (in 463 Caucasian individuals), the rs142167 [P = 2.80E-05; OR = 1.61 (1.29-2.02)] and rs9890413 [P = 0.002; OR = 1.4 (1.12-1.74)] SNPs in WNT3 were significantly associated with all clefts (Menezes et al, 2010). Chiquet et al (2008) also discovered significant differences between the phenotypes of the rs9890413 SNP in the WNT3 gene in the European, American, and Hispanic population. These results indicate that the WNT3 gene is associated with NSCL/P.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, Wnt9b is involved in fusion of the medial and lateral nasal processes (Juriloff et al, 2006;Lan et al, 2006;Ferretti et al, 2011). Variation of Wnt genes is associated with non-syndromic cleft lip and/or palate (CLP) in human and mouse studies (Juriloff et al, 2006;Chiquet et al, 2008). Knockdown of zebrafish wnt9a results in an abridged palate, where the bilateral trabeculae are joined in the midline but the ethmoid plate does not extend (Curtin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that WNT genes are associated with cleft lip and palate. Wnt3a, Wnt5a and Wnt11 are differentially expressed in non-syndromic cleft lip with or without cleft palate significantly 30) .…”
Section: Discussionmentioning
confidence: 96%